THE IMPACT OF DIGITAL TECHNOLOGY USE ON THE EFFICIENCY OF FINANCIAL MANAGEMENT IN SMALL ENTERPRISES - Paulus Tahu, Gregorius (Pena Cendekia Insani, 2026)
A well-written abstract helps the reader to rapidly and precisely grasp the main This study aims to analyze the implementation of digital technology in small business financial management, identify its impact on efficiency, and uncover the factors and challenges influencing its adoption. Using a mixed-methods approach (quantitative and qualitative), primary data were obtained through surveys and interviews with small business owners, while secondary data were drawn from relevant literature and financial reports. Descriptive and comparative analyses were conducted to compare financial management conditions before and after the implementation of digital technology. The results show that the adoption of digital tools, such as accounting software and online financial applications, improves efficiency in transaction recording, financial analysis, and report generation. Small businesses using these technologies reported a 25% reduction in administrative costs and a 30% increase in productivity. However, challenges such as high implementation costs, low digital literacy, and limited infrastructure remain major obstacles. Factors influencing adoption include user education, trust in technology, and prior user experience. In conclusion, digital technology significantly contributes to the efficiency and competitiveness of small enterprises; however, its integration requires support through training, technical assistance, and government subsidies. This study recommends developing affordable and user-friendly technological solutions and fostering collaborative initiatives between the government, technology providers, and business owners to address adoption barriers.